IMPLEMENTATION OF CORETAX IN IMPROVING COMPLIANCE AND EFFICIENCY OF TAX ADMINISTRATION AT KP2KP BATUSANGKAR - Helma Shintia; Nasfizar Guspendri (Jurnal Akuntansi Syariah (JAkSya), 2025)
This study examines the challenges of CoreTax implementation at KP2KP Batusangkar, including limited technological infrastructure, low understanding of taxpayers toward digital tax systems, and the lack of optimal adaptation among tax officers. This study aims to analyze the implementation of CoreTax in improving taxpayer compliance and administrative efficiency at KP2KP Batusangkar. This study uses a qualitative descriptive method with field research design. The data sources consist of primary data obtained from interviews with tax officers and corporate taxpayers, and secondary data derived from official regulations, documentation, and related literature. The results show that the implementation of CoreTax has generally run well and contributes positively to improving taxpayer compliance and administrative efficiency. CoreTax simplifies the reporting process, minimizes administrative errors, and enhances service transparency through an integrated digital system. However, technical disturbances, limited infrastructure, and the low digital literacy of taxpayers still hinder optimal performance. Continuous socialization, system maintenance, and training for users are required to ensure effective implementation.